2021
DOI: 10.1002/ajim.23282
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an arm‐support exoskeleton on perceived work intensity and musculoskeletal discomfort: An 18‐month field study in automotive assembly

Abstract: Background: Exoskeleton (EXO) technologies are a promising ergonomic intervention to reduce the risk of work-related musculoskeletal disorders, with efficacy supported by laboratory-and field-based studies. However, there is a lack of fieldbased evidence on long-term effects of EXO use on physical demands.Methods: A longitudinal, controlled research design was used to examine the effects of arm-support exoskeleton (ASE) use on perceived physical demands during overhead work at nine automotive manufacturing fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 45 publications
(75 reference statements)
3
25
1
Order By: Relevance
“…16,19 We also reported earlier that there were only slightly lower musculoskeletal discomfort scores reported for the neck and shoulder in a group that used an ASE (vs no ASE) during automotive assembly work. 21 The current results agree with those earlier reports, in that the current participants reported the same or slight better perceived safety and job performance using an ASE (Fig. 2).…”
Section: Effectiveness Of An Ase In Reducing Physical Demands On the ...supporting
confidence: 93%
See 3 more Smart Citations
“…16,19 We also reported earlier that there were only slightly lower musculoskeletal discomfort scores reported for the neck and shoulder in a group that used an ASE (vs no ASE) during automotive assembly work. 21 The current results agree with those earlier reports, in that the current participants reported the same or slight better perceived safety and job performance using an ASE (Fig. 2).…”
Section: Effectiveness Of An Ase In Reducing Physical Demands On the ...supporting
confidence: 93%
“…Interestingly, though, De Bock et al 19 compared the impacts of using an ASE between laboratory and actual work environments, finding that the magnitude of beneficial effects of ASE use was smaller in the latter. We also observed relatively small, positive impacts of using an ASE on neck and shoulder discomfort during an 18-month field test in an automotive assembly environment, 21 which contrasts with more substantial benefits obtained in earlier lab studies that examined the same or other ASEs. 10,22 Earlier field studies also revealed usability and safety concerns that were often not fully identified or understood from labbased studies.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Though limited in number and scope, some field-based studies have been completed, the results of which have identified potential EXO usage concerns that may not be evident in lab-based studies. For example, using an EXO may substantially reduce physical demands in controlled (lab-based) tests, yet in some cases such beneficial effects were smaller in practice (Amandels, Eyndt, Daenen, & Hermans, 2019;De Bock et al, 2021;Kim, Nussbaum, Smets, & Ranganathan, 2021). A longitudinal study reported by Kim et al (2021) examined the use of an arm-support exoskeleton during overhead work in automotive assembly facilities, finding that beneficial effects were only modest and differed across facilities.…”
Section: Introductionmentioning
confidence: 99%